2018
DOI: 10.1038/s41598-018-24514-9
|View full text |Cite
|
Sign up to set email alerts
|

Expression of KK-LC-1, a cancer/testis antigen, at non-tumour sites of the stomach carrying a tumour

Abstract: Kita-Kyushu lung cancer antigen-1 (KK-LC-1) is a cancer/testis antigen (CTA) and predominant target for cancer immunotherapy. Our previous study indicated that KK-LC-1 was expressed in 82% of gastric cancers, and also in 79% of early stage of gastric cancers, with a correlation to Helicobacter pylori (H. pylori) infection. In addition, we found that KK-LC-1 was occasionally expressed at non-tumour sites of stomachs carrying tumours. Here, we investigated the characteristics of KK-LC-1 expression at non-tumour … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 18 publications
2
22
0
Order By: Relevance
“…6 The expression rate of KK-LC-1 in human malignancies is markedly higher than the rates of other CT antigens. 9 KK-LC-1 is cancer cell selective and immunogenic, and expressed at high level and frequency in cancers, 6 making it an ideal cancer immunotherapy target. 9 KK-LC-1 is cancer cell selective and immunogenic, and expressed at high level and frequency in cancers, 6 making it an ideal cancer immunotherapy target.…”
Section: Introductionmentioning
confidence: 99%
“…6 The expression rate of KK-LC-1 in human malignancies is markedly higher than the rates of other CT antigens. 9 KK-LC-1 is cancer cell selective and immunogenic, and expressed at high level and frequency in cancers, 6 making it an ideal cancer immunotherapy target. 9 KK-LC-1 is cancer cell selective and immunogenic, and expressed at high level and frequency in cancers, 6 making it an ideal cancer immunotherapy target.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we found that the overall expression of KK-LC-1 in tumor tissues was signi cantly higher than that in normal tissues, and GC patients with higher KK-LC-1 expression had a better prognosis. Fukuyama et al [29] also found similar results that KK-LC-1 gene expression was higher in tumor regions than in non-tumor regions, and KK-LC-1 was occasionally expressed at non-tumour sites of stomachs carrying tumours. In our experimental results, the expression rate of KK-LC-1 in tumor tissues was 95.7%.…”
Section: Discussionmentioning
confidence: 57%
“…Such an issue may be resolved by sampling multiple mucosa sites from the lower corpus. Supplementary Figure S1 and results from our previous study show that KK-LC-1's expression rate in the lower corpus was of 68.1 and 66.1%, respectively [16].…”
Section: Kk-lc-1's Expression Might Become a New Indicator For Measurmentioning
confidence: 81%
“…Furthermore, in an earlier study, Fukuyama et al clari ed the speci c phenomena at the basis of the correlation between KK-LC-1 expression and Hp infection. Additionally, we previously showed how KK-LC-1 expression was frequently detected at non-tumour sites of the stomach occurring GC [14,16]. However, from these studies, it remained unclear whether KK-LC-1 was expressed in the stomach of patients who were not carrying a tumour and with Hp infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation